A Historical Review of the Artificial Pollination of Vanilla planifolia: The Importance of Collaborative Research in a Changing World - Karremans Lok, Adam Philip (2024)
The natural fertilization of Vanilla planifolia has long been a matter of speculation. Stingless (tribe Meliponini) and orchid bees (tribe Euglossini) are often cited as effective pollinators, but direct evidence is notoriously lacking. As with other food-deceptive orchids, the natural fruit-set in V. planifolia is low and does not occur spontaneously outside its native range in Middle America. Fruiting has, therefore, necessitated human intervention through artificial pollination. How Vanilla first came to be artificially pollinated is a controversial issue spurring egotism and nationalism. There are numerous texts offering differing versions of the historical events that led to the discov-ery of the artificial fertilization of V. planifolia and its propagation as a crop. Historical records show Vanilla was simultaneously being pollinated in several parts of the world. I argue that the suspected independent simultaneous discoveries made in Liège, Paris, Padua, the Dutch colony of Java (Indonesia), and the French insular colonies Réunion (Bourbon), Guadeloupe, and Martinique are not unconnected. I conclude that they can be traced back to a single discoverer whose feat was spread around the globe by a tight network of corresponding naturalists. This view contrasts with previous authors. Finally, current concerns regarding Vanilla pollination and production are ad-dressed, highlighting the need for immediate actions to conserve the genetic diversity of the crop’s wild relatives to attenuate the effect of extreme climates in a changing world. A plea is made to shift the focus to Middle America, stimulating and supporting local research and conservation efforts and the allocation of funds from this billion-dollar industry.